Learning for Jobs - Field, Simon [Mitarbeiter]; Hoeckel, Kathrin [Mitarbeiter]; Kis, Viktoria [Mitarbeiter]; Kuczera, Malgorzata [Mitarbeiter] (OECD Publications, 2010)
"Following a severe recession the need to help young people into work is a major objective for OECD countries and their education systems. [...] Those graduating from vocational programmes need to be equipped not just with the skills that will get them their first job, but also with the broader capacities for the further learning on and off the job [...]" For this reason, high-level workplace skills are considered a key means of supporting economic growth. This OECD report "is designed to help countries make their vocational education and training systems more responsive to labour market needs. It expands the evidence base, identifies a set of policy options and develops tools to appraise VET policy initiatives. OECD is conducting country VET policy reviews in Australia, Austria, Belgium (Flanders), the Czech Republic, Germany, Hungary, Ireland, Korea, Mexico, Norway, Sweden, Switzerland, the United Kingdom (England and Wales) and the United States (South Carolina and Texas). A first report on Chile and a short report on the People's Republic of China have also been prepared." (Hrsg., BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.2.3 Qualifikationsentwicklungen; L 5 Beratung & Orientierung; P 3.2 Lehrpersonal; L 2.1.3 Erfahrungslernen; Berufsbildungssystem; Berufsbildungspolitik; Beziehung Bildungssystem Beschäftigungssystem; Qualifikationsentwicklung; Berufsberatung; Bildungspersonal; Lernen am Arbeitsplatz; Qualitätssicherung; OECD-Staaten